Paleoenvironmental Studies in Southwestern Yukon - Gajewski, Konrad; Bunbury, Joan; Vetter, Mary; Kroeker, Nicole; Khan, Amina H. (ARCTIC, 2014)
The St. Elias Mountain region has occupied an important place in the study of the Quaternary because it presents a relatively accessible non-polar icefield and an array of environments from tundra to boreal forest. Paleoenvironmental studies in southwestern Yukon have documented the broad-scale climatic changes of the past 20 000 years, although few studies exist with well-dated sequences at high temporal resolution. Picea glauca arrived across the entire region around 10 000 years ago; however, the details regarding its migration pathways are not well known. Available records indicate few major changes in the composition of the boreal forest vegetation since that time. A slightly more intense fire regime in the early to mid Holocene has been suggested, but this conclusion is based on only a few studies. Variations in the tree line during the Holocene have been examined, but these studies also lack details. There is no evidence for more extensive grasslands in the area during the Holocene. Paleolimnological studies indicate that changes in populations of aquatic organisms have occurred in response to either Holocene climates or watershed variability. La région du mont St. Elias occupe une place importante dans l’étude du Quaternaire parce qu’elle recèle un champ de glace non polaire relativement accessible ainsi qu’une panoplie d’environnements, allant de la toundra à la forêt boréale. Des études paléoécologiques effectuées dans le sud-ouest du Yukon ont permis de documenter les changements climatiques à grande échelle des 20 000 dernières années, et ce, même s’il existe peu d’études dotées de séquences bien datées de grande résolution temporelle. Picea glauca est arrivée dans toute la région il y a environ 10 000 ans. Cependant, les détails concernant sa voie de migration ne sont pas bien connus. Les données disponibles indiquent peu de changements majeurs dans la composition de la forêt boréale depuis cette période. Un régime des feux un peu plus intense de l’Holocène inférieure à l’Holocène moyen a été ...